Effects of Helicobacter pylori Infection on the Development of Chronic Gastritis - Zhou, Xiaoming; Zhu, Yongming; Liu, Jiayu; Liu, Jindi (Turkish Journal of Gastroenterology, 2023)
Background: Based on the gene expression profiles of gastric epithelial tissue at different stages of Helicobacter pylori-infected gastritis, key long noncoding RNAs and genes in the development of Helicobacter pylori infection-induced gastritis were screened to provide a basis for early diagnosis and treatment. Methods: We downloaded 2 sets of sample data from the database, including gastric epithelial tissue samples from gastritis patients from Bhutan and Dominican, and screened mRNAs in the differentially expressed RNAs of the 2 regions. Mfuzz clustering algorithm was used to screen RNAs related to the 3 stages of chronic gastritis. The competing endogenous RNA (ceRNA) regulation network was constructed, and the selected key RNAs were verified. Samples from Bhutan and Dominican were subdivided into the chronic gastritis/ normal comparison groups, and the differentially expressed RNAs were screened to obtain 1067 overlapping RNAs, containing 21 long noncoding RNAs and 1046 mRNAs. Results: Thirty-eight significant gene ontology functional nodes and 6 expression pattern clusters were obtained. Two ceRNA regulatory networks were constructed, and 4 shared miRNAs (hsa-miR-320b, hsa-miR-320c, hsa-miR-320d, and hsa-miR-155-5p) were obtained. Eleven important long noncoding RNAs (AFAP1-AS1, MIR155HG, LINC00472, and FAM201A) and mRNAs (CASP10, SLC26A2, TRIB1, BMP2K, SCAMP1, TNKS1BP1, and MBOAT2) regulated by these 4 miRNAs were obtained. These results indicated that Helicobacter pylori infection had a certain influence on the development of gastritis. Conclusions: The 11 key RNAs can provide a target for the early diagnosis and treatment of chronic gastritis following Helicobacter pylori infection.